Characterization of Pseudomonas aeruginosa for Effective Bitumen Biodegradation under optimal condition - Majid Hassouni, Dhuha (Wasit Journal for Pure sciences, 2025)
The purpose of this research is to grow bacterial samples from soil collected from bitumen-contaminated areas in Kut City, Iraq, namely from paved roads, these roads are regularly exposed to chemicals, oil and other pollutants, the optimal parameters for asphalt bioremediation mediated by Pseudomonas aeruginosa were pH, temperature and carbon supply it was discovered that under the specified experimental conditions, pH 6 is the perfect pH for Pseudomonas aeruginosa to grow and proliferate in order to cure asphalt. The organism's mass concentration was 1.2 and the ideal temperature for asphalt biodegradation was 25 C. The organism's mass was 1.28 the best carbon sources for asphalt bioremediation were glucose.